Molecular regulation of lipogenesis, adipogenesis and fat deposition in chicken - Nematbakhsh, Sara; Chong, Pei Pei; Selamat, Jinap; Nordin, Noordiana; Idris, Lokman Hakim; Abdull Razis, Ahmad Faizal (MDPI AG, 2021)
In the poultry industry, excessive fat deposition is considered an undesirable factor, affecting feed efficiency, meat production cost, meat quality, and consumer’s health. Efforts to reduce fat deposition in economically important animals, such as chicken, can be made through different strategies; including genetic selection, feeding strategies, housing, and environmental strategies, as well as hormone supplementation. Recent investigations at the molecular level have revealed the significant role of the transcriptional and post-transcriptional regulatory networks and their interaction on modulating fat metabolism in chickens. At the transcriptional level, different transcription factors are known to regulate the expression of lipogenic and adipogenic genes through various signaling pathways, affecting chicken fat metabolism. Alternatively, at the post-transcriptional level, the regulatory mechanism of microRNAs (miRNAs) on lipid metabolism and deposition has added a promising dimension to understand the structural and functional regulatory mechanism of lipid metabolism in chicken. Therefore, this review focuses on the progress made in unraveling the molecular function of genes, transcription factors, and more notably significant miRNAs responsible for regulating adipogenesis, lipogenesis, and fat deposition in chicken. Moreover, a better understanding of the molecular regulation of lipid metabolism will give researchers novel insights to use functional molecular markers, such as miRNAs, for selection against excessive fat deposition to improve chicken production efficiency and meat quality.